Quality in higher education: an evaluation in a graduation course in administration at a large university in the municipality of São Paulo - Silva, Alexandre Mendes da; Gouvêa, Maria Aparecida; Semensato, Bárbara Ilze; Pereira, Fernando Antonio de Melo (Revista de Administração da UFSM, 2022)
Objective: to assess the quality perceived by students in the on-site undergraduate course in administration at a private university located in the city of São Paulo, using a new scale developed from the skills expected in the training of future administrators. Design/Methodology/Approach: a 46-item questionnaire was developed and tested, with multivariate statistical techniques (exploratory factor analysis and Cronbach's alpha). In total, 629 students participated in the study. Results: the study identified four blocks of competences: managerial skills, problem solving, proactivity, communication, and creativity and techniques. In the global assessment of the quality of educational services, the institution achieved 76.19%, which indicates that the Administration course offered by the institution can be considered of good quality. The work delivers an instrument and an evaluation methodology that can be used to improve administration courses in the country. Originality/value: the study is relevant when assessing the quality of higher education from a new scale based on the skills required to exercise the profession of an administrator defined by Resolution No. 4 of July 13th, 2005.